Recuerdos de Nuestro Pasado. Issue 3 (3rd July 2019) - Segal, Erin; Malekoff, Andrew
ABSTRACT: Following is an interview with Erin Segal, group worker and coauthor of Recuerdos de Nuestro Pasado (Memories of our Past), a multivocal memoir about growing up in El Salvador and growing old in Washington DC, which emerged from a storytelling group at Mary's Center's Bernice Fonteneau Senior Wellness Center. The group members and coauthors are Angela Celaya, Sergio Guzmán, Jose Lovos, and Gloria Revelo. Using alternating English-language stanzas, the book expresses the life stories of four senior citizens and includes the images of their photographs and objects as well as illustrations by the book designer Julie Cho. Segal and Cho are cofounders of Thick Press. All profit from this book will go to St. Jude Children's Hospital.